Keefektifan Penerapan Model Talking Stick Terhadap Hasil Belajar Tema Cita-Citaku - Wijayanto, Risma Rossyana (Jurnal Ilmiah Sekolah Dasar, 2019)
This study aims to describe the effectiveness of the Talking Stick model to the learning outcomes of students in the theme of the ideals of my fourth grade students at SD N 1 Sukodadi. This research method used is a quasi- experimental method with the research design used was pre experimental design. The sample in this study were 32 students. The results of data analysis showed that the learning outcomes of students in the posttest in the experimental class were effectively used at 0,14. This mean learning by applying an effective Talking Stick model with high criteria towards learning outcomes of class IV students in learning the theme of my ideals at SD N 1 Sukodadi.